PENERAPAN MANAJEMEN SUMBER DAYA MANUSIA (MSDM) DALAM MENINGKATKAN KINERJA GURU DI SMK YASMIDA AMBARAWA KABUPATEN PRINGSEWU - Qoni’ah, Nurul; Irawan, Dedi; Purwanti, Eri (JURNAL MANAJEMEN PENDIDIKAN ISLAM AL-IDARAH, 2017)
His study aims to improve teacher performance in SMK YASMIDA Ambarawa Kab. Pringsewu through the application of Human Resource Management. This research is a qualitative research by using a benchmark as a barometer of truth. Objects studied at SMK YASMIDA Ambarawa Kab. Pringsewu. While the data collection techniques applied by using: Interview / interview to the principal, the division of questionnaires / questioners to students and teachers, as well as documentation as supporting research results. The analytical technique used by the authors in this study is descriptive qualitative analysis. From the analysis of the data can be concluded that: The results of research on the implementation process of Human Resource Management (MSDM) is Applying Planning, Organizing, Actuating, and Controlling. Once known the application of POAC hence can be seen an improvement on teacher performance of SMK YASMIDA Ambarawa Kab. Pringsewu is calculated from 2014, 2015 and 2016. The improvement of teacher performance can be seen from the improvement of presentation of the results of implementation on each statement, with the final result obtained as follows: (a) the result of questionnaire distribution to students with the average obtained in the year 2014 with a presentation value of 62%, in 2015 with a presentation rate of 77% and in 2016 with an 89% presentation. (B) the results of questionnaire distribution to teachers with an average score obtained in 2014 with a presentation value of 60%, in 2015 with a presentation value of 68% and in 2016 with a presentation value of 89%.